Cancer risks in first degree relatives of BRCA1 mutation carriers: effects of mutation and proband disease status. Issue 5 (14th October 2005) - Gronwald, J; Huzarski, T; Byrski, B; Medrek, K; Menkiszak, J; Monteiro, A N; Sun, P; Lubinski, J; Narod, S A
Abstract : Background: Mutations in the BRCA1 (MIM 113705) gene are found in many families with multiple cases of breast and ovarian cancer, and women with a BRCA1 mutation are at significantly higher risk of developing breast and ovarian cancer than are the general public. Methods: We obtained blood samples and pedigree information from 3568 unselected cases of early-onset breast cancer and 609 unselected patients with ovarian cancer from hospitals throughout Poland. Genetic testing was performed for three founder BRCA1 mutations. We also calculated the risk of breast and ovarian cancer to age 75 in the first degree relatives of carriers using Kaplan-Meier methods. Results: The three founder BRCA1 mutations were identified in 273 samples (187 with 5382insC, 22 with 4153delA, and 64 with C61G). A mutation was present in 4.3% of patients with breast cancer and 12.3% of patients with ovarian cancer. The overall risk of breast cancer to age 75 in relatives was 33% and the risk of ovarian cancer was 15%. The risk for breast cancer was 42% higher among first degree relatives of carriers of the C61G missense mutation compared to other mutations (HR = 1.42; p = 0.10) and the risk for ovarian cancer was lower than average (OR = 0.26; p = 0.03). Relatives of women diagnosed with breast cancer had a higher risk of breast cancer than relatives of women diagnosed with ovarian cancer (OR = 1.7; p = 0.03). Conclusions: The risk of breast cancer in female relatives of women with a BRCA1 mutation depends on whether the proband was diagnosed with breast or ovarian cancer.